Information Technology in Nepal: History and Current Status - Khanal, Bishnu Prasad (Curriculum Development Journal, 2024)
This paper provides a comprehensive analysis of the evolution and present state of Information Technology (IT) in Nepal, tracing its roots from introducing the f irst electronic calculator in 1961 for census calculations to its current role as a significant contributor to the national economy. Convergence of Information Technology has reshaped various sectors in Nepal, from banking and commerce to education and media. This study outlines key milestones in the evolution of IT, such as the establishment of Nepal Bank Limited’s computerized systems, the rise of digital media, and the increasing use of online services across different industries. It also delves into government policies and the role of the private sector in accelerating IT adoption. This study utilizes a mixed-methods approach, combining quantitative analysis of IT export growth with qualitative insights into government policies and the socio-economic impacts of Nepal’s IT sector. By exploring the historical context and evaluating the current challenges and opportunities in Nepal’s IT sector. This paper offers recommendations for sustaining and expanding the growth of IT as a catalyst for development. The findings highlight that continued investment in IT infrastructure and improved policies can further boost Nepal’s economic growth, innovation, and education.